2019
DOI: 10.4236/jfcmv.2019.71003
|View full text |Cite
|
Sign up to set email alerts
|

Prototype of an Echo-PIV Method for Use in Underwater Nuclear Decommissioning Inspections

Abstract: The ongoing decommissioning of the Fukushima Daiichi (1F) nuclear power plant requires the inspection of the inside of containment vessels that have been submerged in water. These inspections must locate leaks and map the distribution of fuel debris in water with very low visibility. This paper reports the design and testing of an echo-PIV system that uses a single divergent signal wave and delay-and-sum processing to efficiently map the interior and fluid flow within a submerged vessel. The diverging wave and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…In their research, Kawachi et al demonstrated the design and testing of an echo-PIV system that efficiently mapped the interior and fluid flow of a submerged vessel using a single divergent signal wave and delay-and-sum processing. However, the DW-DAS echo-PIV method is not useful for sensing leakage points and underwater debris at relatively short distances and over a narrow field of view [3]. Meanwhile, Shostak et al proposed a new method for estimating the distance to any underwater object or physical phenomenon by analyzing the curvature of the wavefront and its impact on the measuring sonar system of correlated noise.…”
Section: Introductionmentioning
confidence: 99%
“…In their research, Kawachi et al demonstrated the design and testing of an echo-PIV system that efficiently mapped the interior and fluid flow of a submerged vessel using a single divergent signal wave and delay-and-sum processing. However, the DW-DAS echo-PIV method is not useful for sensing leakage points and underwater debris at relatively short distances and over a narrow field of view [3]. Meanwhile, Shostak et al proposed a new method for estimating the distance to any underwater object or physical phenomenon by analyzing the curvature of the wavefront and its impact on the measuring sonar system of correlated noise.…”
Section: Introductionmentioning
confidence: 99%